2010
DOI: 10.1074/mcp.m110.000075
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, In-solution Separation of Endogenous Cardiac Sarcomeric Proteins and Identification of Distinct Charged Variants of Regulatory Light Chain

Abstract: The molecular conformation of the cardiac myosin motor is modulated by intermolecular interactions among the heavy chain, the light chains, myosin binding protein-C, and titin and is governed by post-translational modifications (PTMs). In-gel digestion followed by LC/MS/MS has classically been applied to identify cardiac sarcomeric PTMs; however, this approach is limited by protein size, pI, and difficulties in peptide extraction. We report a solution-based work flow for global separation of endogenous cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 49 publications
(52 reference statements)
2
55
0
Order By: Relevance
“…Thus, our studies offer insights and tools (computational and mouse models) to expand our understanding of how variations in myosin cycling kinetics across the heart wall contribute to decreased subendocardial workload and DCM. This is important, since we highlight a direct and early influence of loss of Mlc2v phosphorylation in heart disease and failure in vivo (Figure 2), suggesting a direct contribution of dysregulation of MLC2v phosphorylation in human cardiomyopathy and failure (6,8,(10)(11)(12)(13)(14). Recent studies suggest that the MLCK family of "cytoskeletal protein kinases," which target Mlc2v phosphorylation, might also have a broader role in mechanosignaling (43) and thus future studies focused on determining whether strain modulation of cardiac Mlck activity is a potential contributing factor to the mechanisms and outcomes highlighted by our models are warranted.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our studies offer insights and tools (computational and mouse models) to expand our understanding of how variations in myosin cycling kinetics across the heart wall contribute to decreased subendocardial workload and DCM. This is important, since we highlight a direct and early influence of loss of Mlc2v phosphorylation in heart disease and failure in vivo (Figure 2), suggesting a direct contribution of dysregulation of MLC2v phosphorylation in human cardiomyopathy and failure (6,8,(10)(11)(12)(13)(14). Recent studies suggest that the MLCK family of "cytoskeletal protein kinases," which target Mlc2v phosphorylation, might also have a broader role in mechanosignaling (43) and thus future studies focused on determining whether strain modulation of cardiac Mlck activity is a potential contributing factor to the mechanisms and outcomes highlighted by our models are warranted.…”
Section: Figurementioning
confidence: 99%
“…Understanding the molecular actions of MLC2v phosphorylation in the regulation of actin-myosin interaction kinetics in cardiac muscle is of key importance, since emerging evidence in humans suggests a critical role for MLC2v in human health. Several studies have shown that dysregulation of MLC2v via dephosphorylation is associated with human cardiomyopathies and heart failure (6,8,(10)(11)(12)(13)(14); however, mechanistic insights into its underlying role in heart disease still remain elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3F). Our laboratory has shown that ablation of MLC2 phosphorylation decreases ventricular power, lengthens the duration of ventricular ejection, and may also modify other sarcomeric proteins (e.g., cardiac troponins) as substrates for kinases and phosphatases (21)(22)(23). The other differences that may be of significance are that Tm phosphorylation fell significantly with I/R in WT but not in Pak-KO hearts, and TnT phosphorylation increased with I/R in WT but not in Pak-KO.…”
Section: Discussionmentioning
confidence: 77%
“…However, human ventricular RLC may only be singly phosphorylated (Ser-15) (Fig. 1) or singly deamidated (Asn-14 to Asp-14) (Scruggs et al 2010;Scruggs and Solaro 2011). These sites are mostly phosphorylated by a cardiac-specific MLCK (cMLCK), encoded by MYLK3, which, in addition to its role in Ca 2+ sensitization of myofilaments (Sweeney and Stull 1986), may serve as an adaptive mechanism to rapidly facilitate sarcomere organization in cardiac myocytes in response to hypertrophic stimuli associated with increased intracellular Ca 2+ (Aoki et al 2000).…”
Section: Introductionmentioning
confidence: 99%